(untitled) (New York, 1991)
The reception accorded the authors' Habits of the Heart ( LJ 3/1/85) should assure a cordial welcome for this follow-up volume. In it, the authors observe that people are losing trust in their institutions--governmental, religious, business, educational, etc.--and maintain that a more active participation by an enlightened citizenry in institutional affairs is essential for the well-being not only of America but of the world. They claim that large-scale institutions are amenable to citizen action and the influence of global opinion. The book is packed with vigorous thinking, and its value as a harsh stimulant cannot be denied. The one defect is that it is perhaps better fitted to arouse people on the need for asserting themselves than to assist them in the task of doing so. For readers who are seriously interested in societal problems.
Keywords: United states,United states,United states; Civilization,Economic conditions,Social conditions; 1970-,1981-,1980-